Complex and Novel Arrhythmias Precede Stillbirth in Fetuses With De Novo Long QT Syndrome. (May 2020) - Strand, Sarah; Strasburger, Janette F.; Cuneo, Bettina F.; Wakai, Ronald T.
Abstract : Background: Long QT syndrome (LQTS) is a leading cause of sudden cardiac death in early life and has been implicated in ≈10% of sudden infant deaths and unexplained stillbirths. The purpose of our study was to use fetal magnetocardiography to characterize the electrophysiology and rhythm phenotypes of fetuses with de novo and inherited LQTS variants and identify risk factors for sudden death before birth. Methods: We reviewed the fetal magnetocardiography database from the University of Wisconsin Biomagnetism Laboratory for fetuses with confirmed LQTS. We assessed waveform intervals, heart rate, and rhythm, including the signature LQTS rhythms: functional 2° atrioventricular block, T-wave alternans, and torsade de pointes (TdP). Results: Thirty-nine fetuses had pathogenic variants in LQTS genes: 27 carried the family variant, 11 had de novo variants, and 1 was indeterminate. De novo variants, especially de novo SCN5A variants, were strongly associated with a severe rhythm phenotype and perinatal death: 9 (82%) showed signature LQTS rhythms, 6 (55%) showed TdP, 5 (45%) were stillborn, and 1 (9%) died in infancy. Those that died exhibited novel fetal rhythms, including atrioventricular block with 3:1 conduction ratio, QRS alternans in 2:1 atrioventricular block, long-cycle length TdP, and slow monomorphic ventricular tachycardia. Premature ventricular contractions were also strongly associated with TdP and perinatal death. Fetuses with familial variants showed a lower incidence of signature LQTS rhythm (6/27=22%), including TdP (3/27=11%). All were live born. Conclusions: The malignancy of de novo LQTS variants was remarkably high and demonstrate that these mutations are a significant cause of stillbirth. Their ability to manifest rhythms not known to be associated with LQTS increases the difficulty of echocardiographic diagnosis and decreases the likelihood that a resultant fetal loss is attributed to LQTS. Registration: URL: http://www.clinicaltrials.gov . Unique identifier: NCT03047161.